QIRAAH MUBADALAH: SOLUTION TO DOMESTIC VIOLENCE - Muthohar, Muhammad Amin; Cholil, Mufidah; Rizki, Kamalia Fitri (istinbath, 2025)
The study of domestic violence is very important to discuss because with the existence of domestic violence, various new thoughts and solutions emerge, one of which is qiraah mubadalah. This article aims to describe domestic violence, the involvement of power in domestic violence, and qiraah mubadalah as a solution to domestic violence. This research is in the form of library science research or literature using qualitative methods. The results of this study are: Domestic violence can be defined as domestic violence can be defined as an act against a person, especially a woman, which causes physical, sexual, psychological, and/or domestic neglect. It also includes threats to commit such acts, coercion, or unlawful deprivation of liberty within the scope of the household. The dominance of power is also very influential in domestic violence because, with the power held by someone, other people in the social strata will submit to the owner of the power. Qiraah mubadalah can be a solution when domestic violence cases occur through the principles of mitsaqan ghalidzo, hunna libasun lakum wa antum libasun lahunna, muasyarah bil maruf, tasyawurin, and Taradhim min huma.